MULTIMEDIA-BASED TRAINING TO IMPROVE UNDERSTANDING OF ENGLISH FOR SPECIAL WORK EXCHANGE PREPARATION PARTICIPANTS - Purwanto, Tato; Rukanda, Nandang (IKIP Siliwangi Bandung, 2024)
This study aims to determine the use of multimedia in learning English for students. The use of multimedia should be able to meet the needs of the students and can make the students easier to understand the questions during the selection and preparation of SPECIAL JOB EXCHANGE . This research uses descriptive qualitative research. Data collection techniques used observation, interview, and documentation. The results of this study are (1) Design English language learning by using multimedia created by the teacher aims to help the learning process of students either short term or longterm (2) the implementation of multimedia can be done well. It can be seen from the active learning in the learning activity, (3) the attitude of the students in achieving the acceptance of the learning materials by utilizing the multimedia based on the observation is that the students become more interested and feel happy in learning activities, is active, and enthusiastic, It can be concluded that the use of multimedia in teaching and learning English for the selection of participants Special Job ExchangeÂ goes well because it can make the students to improve motivation so that students become enthusiastic in the process of learning